Pendampingan Rumah Produksi Telur Asin Pak Jaini Desa Masangan Kulon, Kecamatan Sukodono, Kabupaten Sidoarjo - Mala, Asnal; Fatimatuzzahro, Siti (Jurnal Pengabdian Masyarakat (JUDIMAS), 2024)
The mentoring program for Pak Jaini's salted egg production house in Masangankulon Village, Sukodono District, Sidoarjo Regency is an initiative to improve the quality and capacity of local production. This activity aims to assist Mr Jaini in developing his business through the application of simple technology, business management training, and effective marketing strategies. The methods used in the mentoring programme include observation, interviews, and hands-on training in the field. The results of this mentoring programme showed significant improvements in product quality, production efficiency, and sales. Thus, this programme is expected to make a positive contribution to the local economy and become a model for other small and medium enterprises in the region